Sepeda Treadmill Menggunakan Penggerak Motor Listrik - Edilla Edilla; Roni Novison; Danu Wirndo (Politeknik Caltex Riau, 2020)
Bicycle Treadmill is a two-wheeled bicycle and has a treadmill that uses a brushless motor as the power of the treadmill bike. A treadmill bike is used with a rider walking on a treadmill that has been provided. The speed of a treadmill bike can be adjusted as desired by adjusting the brushless motor speed using the throttle gas provided on the treadmill bicycle handlebars. The treadmill is not only flat, but there is also a slope angle that can help relieve the treadmill when the rider rides a treadmill bike and increases the treadmill's launch power. This aims to facilitate users when using a treadmill bike like a treadmill in a fitness center. A treadmill that has a battery capacity of 52 Volts can travel a maximum distance of up to 38.4 Km. Brushless motor with 350 Watts of power can be driven by riders with a maximum weight of 115 Kg. The brushless motor that is used on treadmill bikes requires a current average of 4.362 A with a starting current of 10.776 A. Based on the times, bicycle treadmill is the latest development of sports methods from ordinary bikes or electric bikes that are no longer pedaled but walk or run on a treadmill provided.